On Henry van de Velde's Manuscript on Ornament - Haddad, Elie G. (2003)
This article discusses Henry van de Velde's unpublished Manuscript on Ornament, which I have reassembled from various fragments in his archives. 1 Henry van de Velde is known principally for his role in the development of Art Nouveau in Belgium and Germany around the tum of the twentieth centure, and for his polemical role in the ‘Werkbund’ conference in cologne in 1914, which later came down in history as a reactinary attempt to oppose the historical progress of modernism. What is leess well known, or even ignored, is the role that van de Velde played in elaborating an aesthetic theory a synthesis of the two opposite poles of rational conception associated with particular understanding of the ornamental function. The Manuscript on Ornament sheds furthur light on this aesthetic thory, and the role played therein by the notion of ornament. It constitutes therefore an important document in the sequence of his intention of publishing a ‘historical—theoretical’ treatise on ornament. It is true that throughtout his earlier publications he touched on this issue from different angles, but nowhere did he set out to produce a document such as this one [1].